Implementasi Aplikasi E-Katalog Lokal Perangkat Daerah Kabupaten Gorontalo Utara - Angraini, Feni; Aneta, Asna; Ahmad, Muhtar (Innovative: Journal Of Social Science Research, 2024)
In the government's efforts through modernization of procurement, namely by procuring goods and services through E-Purchasing. The purpose of this research is to find out how the implementation of the E-catalog application of North Gorontalo Regency Regional Devices. The research used a qualitative approach with descriptive methods. Data collection techniques Observation, Interview and Documentation. The results showed that (1) Communication established in the implementation of local E-catalog implementation in North Gorontalo Regency has not been fully implemented as a whole, (2) Human resources who have competence in the field of goods and services procurement are still very few. (3) Good disposition/attitude has been applied in the implementation process of the local e-catalog application for regional equipment in North Gorontalo Regency. (4) In the bureaucratic structure, the division of tasks in implementing the E-catalog application is very clear but uneven, the existence of SOPs has also been very helpful for regional apparatus to carry out the implementation of the E-catalog application. Keyword:E-Catalog, Procurement, Implementation